Dialectics of English Linguistics - Raja Ambethkar M, Dr; K B Glory, Dr (International Journal of Engineering and Technology, 2018)
The research article “DIALECTICS OF ENGLISH LINGUISTICS” is an outcome of the direct study and observation of the use of English, of the teaching faculty at about 21 colleges, particularly Engineering colleges in Coastal Andhra area. It intends to expose various dialectics of English as a second language, identify redundant usage and use effective English. Change of trends in meaning and usage occurs mainly in the two components of communication, namely vocabulary and grammar, due to lack of clear understanding of Syntax and Semantics. Form of words like heterophones, besides other forms, confuses the learners. Confusion over the use of the American, the Australian, the British and the Indian English, in pronunciation, spelling as well as meaning: Word such as ‘Offing’ to mean ‘likely to happen soon’ is quite misleading. Exposure to Mass Usage has great influence on pronunciation of words by the masses and media Ex. Koombing, ‘baeverse’ etc. Bilingual errors, the result of undue influence of mother tongue, is a proven case, in all Indian States. Similarly the use of double positives, wrong association of words, double negatives, and mistaken negatives as positives has become the worst cases of mass influence. Use of colloquial or slang words due to interaction with people from different regions on account of L.P.G, result in assimilation, integration of this class of vocabulary, percolating subconsciously by the process of osmosis. Lack of suitable vocabulary, among English professionals ranging from lecturers to professionals, lead to monotonous use of words. For example, the word “beautiful” is used to describe many nouns.
Keywords: Dialectics; language; influence; communication; pronunciation.